2006
DOI: 10.1038/nn1662
|View full text |Cite
|
Sign up to set email alerts
|

Selective enhancement of associative learning by microstimulation of the anterior caudate

Abstract: Primates have the remarkable ability to rapidly adjust or modify associations between visual cues and specific motor responses. Whereas little is known as to how such adjustments in behavioral policy are implemented, recent learning models suggest that the anterior striatum is optimally positioned to have a role in this process. We recorded from single units and delivered microstimulation in the striatum of rhesus monkeys performing an associative learning task. Caudate activity during reinforcement was closel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
191
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(211 citation statements)
references
References 28 publications
18
191
1
1
Order By: Relevance
“…result, we failed to observe rapid changes in neural activity during initial learning, as has been reported previously in studies that examined neural correlates of associative learning using procedurally familiar tasks (Brasted and Wise, 2004;Pasupathy and Miller, 2005;Williams and Eskandar, 2006;). Learningrelated changes in neural activity were observed at the time of response initiation (Fig.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…result, we failed to observe rapid changes in neural activity during initial learning, as has been reported previously in studies that examined neural correlates of associative learning using procedurally familiar tasks (Brasted and Wise, 2004;Pasupathy and Miller, 2005;Williams and Eskandar, 2006;). Learningrelated changes in neural activity were observed at the time of response initiation (Fig.…”
Section: Discussionsupporting
confidence: 72%
“…Dorsomedial neurons represent arbitrary associations between stimuli and responses and adjust firing rates rapidly following changes in task contingencies (Brasted and Wise, 2004;Pasupathy and Miller, 2005;Watanabe and Hikosaka, 2005;Williams and Eskandar, 2006;). All of the above studies were done in animals with extensive experience with the task procedure.…”
Section: The Neural Basis Of Reversal Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies in mammals have shown that basal ganglia neurons change their task-related firing during learning (52,53), and that such changes can precede changes in cortical activity and behavior (54)(55)(56). Here, we extend these findings by directly demonstrating that the basal ganglia are required for specific, task-related cortical firing patterns that are critical for song motor plasticity.…”
Section: Discussionsupporting
confidence: 66%
“…A case study of bilateral stimulation of the ventromedial nuclei of the hypothalamus in a human induce sensations of déjà vu, vague flashes of memory, and appeared to show improved hippocampal-dependent memory [53]. High-frequency (200 Hz) electrical stimulation of the caudate, striatum or anterior cingulate during reinforcement might accelerate learning acquisition [171]. The hippocampus itself can be a target of open-loop stimulation: in-vivo stimulation given at 5 Hz (i.e., in the theta range) has been found to induce stable LTP in rats [147].…”
Section: Subcortical and Peripheral Stimulationmentioning
confidence: 99%